“Food Addiction” in Patients with Eating Disorders is Associated with Negative Urgency and Difficulties to Focus on Long-Term Goals - Wolz, Ines; Hilker, Ines; Granero, Roser; Jiménez-Murcia, Susana; Gearhardt, Ashley N.; Dieguez, Carlos; Casanueva, Felipe F.; Crujeiras, Ana B.; Menchón, José M.; Fernández-Aranda, Fernando (Frontiers in Psychology, 2016)
Objectives: The present study aimed to investigate if eating disorder patients differ in specific personality traits depending on a positive screening of food addiction and to find a model to predict food addiction in eating disorder patients using measures of personality and impulsivity. Methods: 278 patients having an eating disorder self-reported on food addiction, impulsivity, personality, eating and general psychopathology. Patients were then split into two groups, depending on a positive or negative result on the food addiction screening. Analysis of variance was used to compare means between the two groups. Stepwise binary logistic regression was used to obtain a predictive model for the presence of food addiction. Results: Patients with food addiction had lower self-directedness, and more negative urgency and lack of perseverance than patients not reporting addictive eating. The probability of food addiction can be predicted by high negative urgency, high reward dependence, and low lack of premeditation. Conclusions: Eating disorder patients who have more problems to pursue tasks to the end and to focus on long-term goals seem to be more likely to develop addictive eating patterns.